Compartmental Pharmacokinetics and Tissue Distribution of the Antifungal Echinocandin Lipopeptide Micafungin (FK463) in Rabbits - Groll, Andreas H. (American Society for Microbiology, 2001)
The plasma pharmacokinetics and tissue distribution of the novel antifungal echinocandin-like lipopeptide micafungin (FK463) were investigated in healthy rabbits. Cohorts of three animals each received micafungin at 0.5, 1, and 2 mg/kg of body weight intravenously once daily for a total of 8 days. Serial plasma samples were collected on days 1 and 7, and tissue samples were obtained 30 min after the eighth dose. Drug concentrations were determined by validated high-performance liquid chromatographic methods. Plasma drug concentration data were fit to a two-compartment pharmacokinetic model, and pharmacokinetic parameters were estimated using weighted nonlinear least-square regression analysis. Micafungin demonstrated linear plasma pharmacokinetics without changes in total clearance and dose-normalized area under the concentration-time curve from 0 h to infinity. After administration of single doses to the rabbits, mean peak plasma drug concentrations ranged from 7.62 μg/ml at 0.5 mg/kg to 16.8 μg/ml at 2 mg/kg, the area under the concentration-time curve from 0 to 24 h ranged from 5.66 to 21.79 μg · h/ml, the apparent volume of distribution at steady state ranged from 0.296 to 0.343 liter/kg, and the elimination half-life ranged from 2.97 to 3.20 h, respectively. No significant changes in pharmacokinetic parameters and no accumulation was noted after multiple dosing. Mean tissue micafungin concentrations 30 min after the last of eight daily doses were highest in the lung (2.26 to 11.76 μg/g), liver (2.05 to 8.82 μg/g), spleen (1.87 to 9.05 μg/g), and kidney (1.40 to 6.12 μg/g). While micafungin was not detectable in cerebrospinal fluid, the concentration in brain tissue ranged from 0.08 to 0.18 μg/g. These findings indicate linear disposition of micafungin at dosages of 0.5 to 2 mg/kg and achievement of potentially therapeutic drug concentrations in plasma and tissues that are common sites of invasive fungal infections.